An investigation into the molecular mechanism of action of the progestins, medroxyprogesterone acetate and norethisterone acetate - Koubovec, Dominique J. B. M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2004.